2018
DOI: 10.14444/5041
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic Ossification After Cervical Total Disc Replacement at 7 Years—Prevalence, Progression, Clinical Implications, and Risk Factors

Abstract: Background: Heterotopic ossification (HO) is a known risk following cervical total disc replacement (CTDR) surgery, but the cause and effect of HO are not well understood. Reported HO rates vary, and few studies are specifically designed to report HO. The effects on outcomes, and the risk factors for the development of HO have been hypothesized and reported in small-population, retrospective analyses, using univariate statistics.Methods: Posthoc, multiple-phase analysis of radiographic, clinical, and demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 42 publications
3
22
0
1
Order By: Relevance
“…These findings are similar to those reported by Nunley et al of combined total grades III or IV at both levels of 37.4% for two-level CDA with a different CDA device at 7 years postoperatively. 22 Nunley et al did find a significant negative cor- relation between HO grade and ROM. In the current study, while there were patients with reported grade III or IV HO and patients with reduced angular motion, these observations were not frequent enough to negatively influence the overall average angular motion at the index levels of CDA patients, which was maintained over time out to 10 years.…”
Section: Discussionmentioning
confidence: 91%
“…These findings are similar to those reported by Nunley et al of combined total grades III or IV at both levels of 37.4% for two-level CDA with a different CDA device at 7 years postoperatively. 22 Nunley et al did find a significant negative cor- relation between HO grade and ROM. In the current study, while there were patients with reported grade III or IV HO and patients with reduced angular motion, these observations were not frequent enough to negatively influence the overall average angular motion at the index levels of CDA patients, which was maintained over time out to 10 years.…”
Section: Discussionmentioning
confidence: 91%
“…Different influencing factors have been identified. Pierce [ 9 ] showed that sex, obesity, and follow-up time were risk factors for HO after CDR, while Michael [ 19 ] and Qi [ 10 ] showed that surgical skill proficiency and facet joint degeneration were associated with HO. Nevertheless, HO is a specific complication of CDR, and there is a lack of analytical data for discussing the correlation between CDR surgical factors and postoperative HO.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of HO after CDR is still not completely clear. Some studies have shown that sex, age, BMI, number of treatment levels, and follow-up time are risk factors for HO [ 9 , 10 ]. However, few studies have investigated the potential role of surgical techniques in HO occurrence following CDR.…”
Section: Introductionmentioning
confidence: 99%
“…В работе P.D. Nunley et al [21] доказано, что мужской пол, ожирение, сохранение элементов замыкательной пластинки, проведение оперативного вмешательства на двух сегментах и степень выраженности болевого синдрома в шейном отделе позвоночника по визуальной аналоговой шкале являются факторами риска развития гетеротопической оссификации в отдаленном послеоперационном периоде. Необходимо отметить, что курение также является доказанным фактором риска высокой частоты встречаемости нежелательных явлений, увеличения продолжительности госпитализации пациентов и снижения скорости образования костной ткани после выполнения операции ригидной стабилизации [10][11][12][13].…”
Section: Discussionunclassified